Visibility study in Seoul, 1993 - Baik, NJ; Kim, YP; Moon, KC (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
Characteristics of visual air quality in Seoul were investigated during the fall of 1993. The total extinction coefficient, b(ext), the particle light scattering coefficient, b(sp), and the particle mass size distribution were measured using a transmissometer, a nephelometer and a cascade impactor, respectively. Also PM1, PM3 and PM10 particles were collected and analyzed for their ionic concentrations. The smog characteristics were also estimated by using a Mie theory based model. Measured and estimated light extinction budgets agree to each other within 10%. According to measurements, the daily average b(ext) were 0.791 x 10(-3) and 0.297 x 10(-3) m(-1) during the smoggy and clear period, respectively. Also b(sp) contributed 79.4 and 55.2% to b(ext) during the smoggy and dear period, respectively, showing that the dominant factor in light extinction during the smog episode. The major variables that affect smog phenomena in Seoul are mass loadings of fine particle fraction (D-p < 2.98 mu m), concentrations of sulfate and nitrate in fine particles, and relative humidity. The particle mass size distribution shows typical bimodal peaks, one of which is at about 0.8 mu m and the other at about 5.0 mu m of the mean diameter during both periods. Particulate sulfate and nitrate are more concentrated in the fine particle size fraction during the smoggy period than in the clear period. The effects of relative humidity are thought to influence the extinction and scattering efficiencies of particle species through changing the particle size. Copyright (C) 1996 Elsevier Science Ltd
Keywords: CHEMICAL-COMPOSITION; AEROSOL; SCATTERING; DENVER; EXTINCTION; DETROIT; MODEL; AREA